New record of Plesiopelma aspidosperma and distribution extension of Cyriocosmus versicolor (Araneae: Theraphosidae) from Argentina - Allegue, Maite (2023)
This work reports a new record of Plesiopelma aspidosperma Ferretti & Barneche, 2013 and a distribution extension of Cyriocosmus versicolor (Simon, 1897) in Parque Nacional Copo, Santiago del Estero province, Argentina. We also present the first published color photograph of a male of Cyriocosmus versicolor. Finally, data on their natural history is provided.